2000
DOI: 10.3923/pjbs.2000.977.982
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on Kojic Acid Fermentation by Aspergillus flavus

Abstract: Abstract:The influence of pH on kojic acid fermentation by Aspergillus flavus Link 44-1 in submerged fermentation and resuspended cell system was investigated separately. Although the highest growth in submerged fermentation was obtained at initial culture pH between 6 to 7, the optimum kojic acid production was achieved at initial culture pH 3. At initial culture pH 2, growth was greatly inhibited and kojic acid was not produced. In resuspended cell system using buffered glucose solution, in which the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
(16 reference statements)
2
7
0
Order By: Relevance
“…Highest obtained yield was 4 g/L at 30 0 C and lowest as 0.2 g/L at 40 0 C. A decrease in Kojic acid concentration with increase in temperature was observed, whereas, 28 0 C was found to be the best temperature by El-Aasar ( 2006) in A. oryzae. Same results are reported by Devi et al, (2014) and Rosfarizan et al, (2010) that an increase in temperature shows signi cant effect on yield of Kojic acid.…”
Section: Effect Of Temperature On a Oryzaesupporting
confidence: 87%
“…Highest obtained yield was 4 g/L at 30 0 C and lowest as 0.2 g/L at 40 0 C. A decrease in Kojic acid concentration with increase in temperature was observed, whereas, 28 0 C was found to be the best temperature by El-Aasar ( 2006) in A. oryzae. Same results are reported by Devi et al, (2014) and Rosfarizan et al, (2010) that an increase in temperature shows signi cant effect on yield of Kojic acid.…”
Section: Effect Of Temperature On a Oryzaesupporting
confidence: 87%
“…Comparably, A. oryzae produces kojic acid at pH 4 73 , in contrast, the kojic acid values appeared in our investigation were not consistent with other reporters, in which the largest amount of kojic acid was obtained from glucose at very acidic pH (1.9 to 3.0) 74 . During growth progress at pH 4.5 to 6, the fungi use enzymes to convert glucose into kojic acid 36 . However, the growth of the fungi was continuous at pH between 2 and 3 the production of kojic acid appeared 75 .…”
Section: Optimization Conditions On Kojic Acid Production By a Flavusmentioning
confidence: 99%
“…Until now, an ample amount of kojic acid has been obtained with the glucose that was used as a carbon source. Most of the Aspergillus and Penicillium species are potent producers of Kojic acid 36 . Among Aspergillus species, Aspergillus flavus being attentive as the maximum producer of Kojic acid.…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that temperature and pH are central criteria for understanding the fungal ecology Ahmed and Naresh [5]. Rosfarizan, et al [22] demonstrated that the highest metabolic activities and cellular growth of filamentous fungi (Aspergillus spp. and Penicillium spp.)…”
Section: Effect Of Temperature On Mycelial Growth Of Aspergillus and Penicillium Speciesmentioning
confidence: 99%